3D printing of bioactive materials for drug delivery applications. (2nd September 2022) - Nasiri, Golara; Ahmadi, Sepideh; Shahbazi, Mohammad-Ali; Nosrati-Siahmazgi, Vahideh; Fatahi, Yousef; Dinarvand, Rassoul; Rabiee, Mohammad; Haftlang, Farahnaz; Kim, Hyoung Seop; Rabiee, Navid
ABSTRACT: Introduction: Three-dimensional (3D) printing, also known as additive manufacturing (AM), is a modern technique/technology, which makes it possible to construct 3D objects from computer-aided design (CAD) digital models. This technology can be used in the progress of drug delivery systems, where porosity has played important role in attaining an acceptable level of biocompatibility and biodegradability with improved therapeutic effects. 3D printing may also provide the user possibility to control the dosage of each ingredient in order to a specific purpose, and makes it probable to improve the formulation of drug delivery systems. Areas covered: This article covers the 3D printing technologies, bioactive materials including natural and synthetic polymers as well as some ceramics and minerals and their roles in drug delivery systems. Expert opinion: This technology is feasible to fabricate drug products by incorporating multiple drugs in different parts in such a mode that these drugs can release from the section at a predetermined rate. Furthermore, this 3D printing technology has the potential to transform personalized therapy to various age-groups by design flexibility and precise dosing. In recent years, the potential use of this technology can be realized in a clinical situation where patients will acquire individualized medicine as per their requirement.